Shared storytelling in Euripidean stichomythia - Schuren, Elisabeth Maria, 1980- (Amsterdam Studies in Classical Philology, 2014)
Long, stichomythic dialogues in the tragedies of Euripides are connected with some of the greatest problems of critical appreciation. The form is considered unnatural particularly when characters use stichomythia to tell stories to each other. In Shared Storytelling in Euripidean Stichomythia Liesbeth Schuren tries to rehabilitate Euripidean stichomythia, using pragmatic and narratological approaches. In the section devoted to pragmatic analysis, comparison between the turn-taking systems in Euripidean stichomythia and naturally occurring conversation establishes to what extent convention and realism are operative. Using narratological arguments, the traditional apparatus is expanded to suit the dialogic nature of narrative stichomythia. Analysis of narrative presentation in storytelling with two interlocutors results in a multi-faceted perspective, an effect unique to narrative stichomythia.